1996
DOI: 10.1128/jcm.34.9.2328-2330.1996
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary paracoccidioidomycosis misdiagnosed as Pneumocystis pneumonia in an immunocompromised host

Abstract: Yeast cells of Paracoccidioides brasiliensis can resemble the cysts of Pneumocystis carinii in smears stained with Grocott's modification of the Gomori methanamine silver stain. Furthermore, P. brasiliensis can crossreact in material stained with a widely used P. carinii immunofluorescent stain which uses monoclonal antibodies. The need to differentiate P. brasiliensis and P. carinii will become more important as the increasing incidence of immunosuppression results in the reactivation of latent P. brasiliensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In the second controlled study, Almeida et al 2016, reported thirty-one HIV-infected patients with PCM between 1993 and 2014 [17]. After compiling the data from these two case-control studies [16,17], two case-series reports [13,18], and 30 single case reports [10,14,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35], we retrieved 136 cases of PCM and HIV coinfection reported in the last 30 years. They aged between 13 and 59 years, with a mean age of 35.9 years.…”
Section: Resultsmentioning
confidence: 99%
“…In the second controlled study, Almeida et al 2016, reported thirty-one HIV-infected patients with PCM between 1993 and 2014 [17]. After compiling the data from these two case-control studies [16,17], two case-series reports [13,18], and 30 single case reports [10,14,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35], we retrieved 136 cases of PCM and HIV coinfection reported in the last 30 years. They aged between 13 and 59 years, with a mean age of 35.9 years.…”
Section: Resultsmentioning
confidence: 99%
“…Only the yeast form, which grows at 35-37 °C, is detected in patients exhibiting PCM (59). Although considerable progress has been made in the diagnosis and treatment of PCM (60)(61)(62), persistent problems exist with respect to antigenic instability (63), crossreactivity and false negative serological results (64), and various other types of misdiagnosis (65)(66)(67)(68). In view of the increasing possibility for of PCM to nonendemic areas (66), as well as the increasing global risk for mycopathogen infection among immunocompromised patients (69-71), the need for improved methods for diagnosis and treatment of PCM and other fungal diseases is clear.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Paracoccidioides takes a spherical, multiple-budding yeast form that resembles that of a ship’s wheel, earning the term “Captain’s Wheel.” However, non-budding or single-budding forms can dominate, which can lead to misdiagnosis [ 18 , 19 ]. Stained with Gomori’s methenamine silver, these atypical forms have been confused with other yeast-like pathogens such as Candida , Cryptococcus , or Pneumocystis [ 18 - 20 ]. In patients presenting with symptoms concerning an endemic fungal infection and an absence of characteristic pathological morphology, serologic testing can be performed using immunodiffusion and complement-fixing methods to detect antibodies against the fungal pathogen in question [ 18 ].…”
Section: Discussionmentioning
confidence: 99%